Interleukin-4 supplementation improves the pathophysiology of hypertension in response to placental ischemia in RUPP rats - Cottrell, Jesse N. (Am J Physiol Regul Integr Comp Physiol, 2019)
Preeclampsia (PE) is characterized by chronic inflammation and elevated agonistic autoantibodies to the angiotensin type 1 receptor (AT(1)-AA), endothelin-1, and uterine artery resistance index (UARI) during pregnancy. Previous studies report an imbalance among immune cells, with T-helper type 2 (Th2) cells being decreased during PE. We hypothesized that interleukin-4 (IL-4) would increase Th2 cells and improve the pathophysiology in response to placental ischemia during pregnancy. IL-4 (600 ng/day) was administered via osmotic minipump on gestational day 14 to normal pregnant (NP) and reduced uterine perfusion pressure (RUPP) rats. Carotid catheters were inserted, and Doppler ultrasound was performed on gestational day 18. Blood pressure (mean arterial pressure), TNF-α, IL-6, AT(1)-AA, natural killer cells, Th2 cells, and B cells were measured on gestational day 19. Mean arterial pressure was 97 ± 2 mmHg in NP (n = 9), 101 ± 3 mmHg in IL-4-treated NP (n = 14), and 137 ± 4 mmHg in RUPP (n = 8) rats and improved to 108 ± 3 mmHg in IL-4-treated RUPP rats (n = 17) (P < 0.05). UARI was 0.5 ± 0.03 in NP and 0.8 in RUPP rats and normalized to 0.5 in IL-4-treated RUPP rats (P < 0.05). Plasma nitrate-nitrite levels increased in IL-4-treated RUPP rats, while placental preproendothelin-1 expression, plasma TNF-α and IL-6, and AT(1)-AA decreased in IL-4-treated RUPP rats compared with untreated RUPP rats (P < 0.05). Circulating B cells and placental cytolytic natural killer cells decreased after IL-4 administration, while Th2 cells increased in IL-4-treated RUPP compared with untreated RUPP rats. This study illustrates that IL-4 decreased inflammation and improved Th2 numbers in RUPP rats and, ultimately, improved hypertension in response to placental ischemia during pregnancy.